Diapause, pollen ball incidence, and overwintering energetics in the alfalfa leafcutting bee, Megachile rotundata - Singh, Preetpal; Rajamohan, Arun; Waybright, Sarah A.; Dillon, Michael E.; Ferrenberg, Scott M.; Rinehart, Joseph P.; Bowsher, Julia H. (Frontiers in Bee Science, 2024)
Warming summer temperatures have the potential to harm managed pollinators, impacting both summer performance and overwintering success. The alfalfa leafcutting bee, Megachile rotundata, is a solitary bee used for commercial pollination of alfalfa. M. rotundata undergoes facultative diapause in the prepupal stage. Prepupae that diapause early in the season are exposed to warm temperatures for a longer period of time than the individuals that start diapause closer to fall, which may reduce lipid reserves required for overwintering survival. Warm temperatures may also contribute to pollen ball incidence, which is when a provision is present but there is no sign of a larva in the brood cell. Our goal was to identify factors that regulate diapause and pollen ball incidence and examine effects of pre-wintering field conditions on post-overwintering energy reserves in M. rotundata. Nest boxes were installed near Fargo, ND, Laramie, WY, and Las Cruces, NM, which exposed bees to different photoperiods and thermal regimes. Three nest boxes were placed at each site. We monitored nesting conditions and diapause and pollen ball incidence throughout the season. Lipids, sugars, and glycogen reserves were measured in adults after overwintering. Our models indicate that most of the variation in diapause incidence was explained by nest, with individuals within a nest tending to have the same diapause outcome. This suggests that the environmental conditions experienced by the mother, or genetic predisposition, influences offspring diapause. We also found evidence that high cavity temperatures can cause diapause aversion. In addition, our study is the first to link high nesting cavity temperatures to increased pollen ball incidence. Exposure to stressful temperatures during development and early diapause resulted in an increase in adult lipid reserves after overwintering. Adult sugar and glycogen reserves were not affected by exposure to warm temperatures during development and early diapause. In conclusion, maternal effects and temperature were important factors for diapause and pollen ball incidence in M. rotundata with macronutrient reserves similar for early and late season bees.